Perbedaan Penentuan Awal Bulan Hijriyah di Indonesia: Tinjauan Integratif Ilmu Falak dan Fiqh Siyasah - Martinus Oktavianus (Jurnal Pelita Nusantara, 2025)
This article seeks to comprehensively examine the epistemological and astronomical roots triggering these differences, as well as to analyze their implications from the perspective of Fiqh Siyasah (Islamic Political Jurisprudence). Through a qualitative approach utilizing a library research design, this study compares various dominant paradigms, ranging from hisab hakiki wujudul hilal, imkanur rukyat (Neo-MABIMS), to the Single Global Hijri Calendar (KHGT). The results indicate that the epistemological root of the differences lies in the dialectic of interpreting rukyat (moon sighting) as a mahdhah worship with a ta'abbudi (textual-ritual) dimension, juxtaposed against the view that rukyat is merely an instrumental tool with a ta'aqquli (contextual-rational) dimension. Astronomically, the divergence is triggered by the starting point of the crescent visibility criteria, particularly the fundamental debate regarding the use of topocentric versus geocentric parameters at a 6.4-degree elongation in Neo-MABIMS, as well as Muhammadiyah's adoption of the new KHGT parameters. In the specific case of the month of Dhul-Hijjah, a sharp clash occurs between the jurisdictions of local matla' (wilayatul hukmi) and global matla' (ittihadul matla'). From the perspective of Fiqh Siyasah, the government authority (ulil amri) through the instrument of the Sidang Isbat (confirmation hearing) does not impose unification in an authoritarian manner, but rather implements a collaborative governance that upholds the freedom of ijtihad. The conclusion of this study emphasizes that the unification of Islamic timekeeping demands a methodological compromise that integrates syar'i validity and scientific certainty, along with the relinquishment of sectoral egos towards the harmonization of a global calendar.